Hemoconcentration induced by exercise: Revisiting the Dill and Costill equation. Issue 6 (30th December 2014) - Alis, R.; Sanchis‐Gomar, F.; Primo‐Carrau, C.; Lozano‐Calve, S.; Dipalo, M.; Aloe, R.; Blesa, J. R.; Romagnoli, M.; Lippi, G.
Abstract : The Dill and Costill equation is used to estimate the exercise‐induced hemoconcentration. However, this calculation requires drawing an extra whole‐blood sample, which cannot be frozen and has to be analyzed with dedicate instrumentation in a relative short time. The aim of the present study was to explore the usefulness of some serum biochemical parameters to estimate hemoconcentration induced by exhaustive exercise. Fourteen healthy male subjects (19–34 years) performed a15‐min running test at 110% of anaerobic threshold speed. Hemoglobin, hematocrit, brain natriuretic peptide (BNP), creatinine, gamma‐glutamyltransferase (GGT), total‐proteins, albumin, total calcium (Ca), K +, Na +, and Cl − were determined in blood samples taken before, after exercise, and after a 30‐min recovery period. Plasma volume loss (ΔPV) was calculated by Dill and Costill equation. At post‐exercise and after recovery, the percentage increments of total‐proteins, albumin, GGT and Ca correlated significantly with ΔPV. Bland–Altman analyses showed that correcting BNP, creatinine, and K + concentration by Ca percentage increments yield biases and limits of agreement that are acceptable when compared with Dill and Costill equation correction. Ca concentration may be used as a hemoconcentration biomarker in high‐intensity exercise, which would allow scientists and physicians avoid extra costs, facilitate in‐field research, and delayed estimation of hemoconcentration using stored serum samples.